Master's and Doctoral Degree Programs to Train Accounting Professors in Brazil: An Analysis of the Pedagogical Components of their Initial Training - Camilla Soueneta Nascimento Nganga; Reiner Alves Botinha; Gilberto José Miranda; Edvalda Araujo Leal (Universidad Autónoma de Madrid, 2016)
The teaching of accounting in Brazil is experiencing transformations, mainly due to the expansion of higher education, the increased number of graduate accounting programs and the adoption of international accounting standards in the country. The Law on National Education Guidelines and Bases (LDB) requires that college professors must have graduate-level training, with priority on master's and doctoral programs. In this context, the main objective of this study was to identify the curriculum components for systematized teacher training that are present in Brazilian graduate programs in accounting. The analysis of the indicators of the referred programs, provided by the Office to Improve University Personnel (CAPES) of the Ministry of Education, revealed a low number of disciplines related to training of future professors offered by the master's and doctoral programs in accounting, as well as wide variation in the offer of graduate teaching assistant positions. This panorama reflects the fact these programs are mainly focused on the development of researchers, with little attention paid to instilling teaching skills in future professors.